Perceived parenting style, online readiness, and self-regulation in online learning among high school students an ecological model - Panlilio, Wallace D. II (College of Education, University of the Philippines Diliman, 2021)
The present study aimed to investigate the relationships and influences among perceived parenting style, online readiness, and self-regulated learning in an online learning environment. A mixed method research design was utilized to determine statistical associations among the main variables to meet this goal. The sample participants consisted of 64 male and female high school students from a Metro Manila school composed chiefly of Filipinos and Filipinos of Chinese descent. Three questionnaires were used: the Parental Authority Questionnaire (PAQ), the Tertiary Students Online Learning Readiness (TSOLR), and the Self-Regulated Online Learning Questionnaire-Revised (SOLQ-R). The study showed the following significant results. Gender showed major differences in technical skills, metacognitive activities before learning, and help-seeking. Grade levels also varied according to technical skills. Metacognitive activities after learning and environment structuring differed according to perceived parenting styles. Help-seeking has significant relationships with attitude towards computers and learning preferences. The theoretical model emerging from this study focused on the critical role of online learning readiness to address online learning's disruptive effect between perceived parenting styles and self-regulated online learning. Educational psychologists, educators, parents, government institutions can help improve students' achievement by making sure that the beneficial impact of perceived parenting styles in developing self-regulated online learning skills is reinforced through higher online learning readiness.